Occupational exposures to hazardous chemicals and agents among healthcare workers in Bhutan. Issue 12 (12th October 2020) - Rai, Rajni; El‐Zaemey, Sonia; Dorji, Nidup; Fritschi, Lin
Abstract: Background: Occupational exposures to hazardous chemicals among healthcare workers can result in long‐term adverse health outcomes. Research on such exposures from low‐ and middle‐income countries is limited. The aim of this study was to estimate the prevalence of exposures to a range of chemicals used in healthcare settings among Bhutanese healthcare workers. Methods: A cross‐sectional study was conducted among healthcare workers ( n = 370) working in three hospitals in the western region of Bhutan. Demographic and occupational information was collected, and exposures to asthmagens, carcinogens, ototoxic and other agents were assessed using a web‐based tool. The prevalence of exposure to these chemicals was calculated and the circumstances resulting in such exposures were examined. Results: The prevalence of exposure to one or more asthmagen, carcinogen, and ototoxic agent was 98.7%, 28.1%, and 7.6%, respectively; and was 6.2% for anesthetic gases and 2.2% for antineoplastic drugs. The most common exposures were to latex, and cleaning and disinfecting agents in the asthmagens group; formaldehyde in the carcinogens group; and p ‐xylene among ototoxic agents. The circumstances resulting in exposures were using latex gloves, using bleach and chlorhexidine for cleaning, using formaldehyde as a disinfectant and in the laboratory, and using p ‐xylene in the laboratory. Conclusions: The results indicate that a large proportion of Bhutanese healthcare workers are occupationally exposed to chemicals linked to chronic diseases, with exposure prevalence higher than in high‐income countries. The study provides information that can be used to formulate policies and to implement control measures to protect healthcare workers.